ANALISIS PENGARUH PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH - Prasetyo, Rudi; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to see the influence level of regional tax revenue and local retribution which is proxy by the pattern of budget target and the pattern of financial revenue which is measured by using its influence on local own source revenue at the local revenue office of Magetan district East Java. As the important institution in the economy therefore the oversight of good performance which has been done by the local revenue commission is required. The data of target financial statement and realization has been obtained from the local own source revenue of of Magetan district and Central Bureau of Statistics (BPS) of Surabaya East Java is started from 2005 to 2014 periods. The sample collection method has been conducted by using purposive sampling. The dependent variable of this research has been carried out by using local own sources revenue whereas the independent variables are local tax and local retribution. The statistic methods which have been conducted in order to analyze the data of local tax revenue and local retribution to the local own source revenue is the data management and the descriptive analysis. The result of data quality test shows that the data has been normally realized. The classic assumption test shows that there is a linear correlation among independent variables in the regression model. The result of goodness of fit test shows that local tax and local retribution is the explanatory variable of the local own sources revenue. Based on the result of linear regressions analysis with its significant level is 5% shows that the result of the research i.e. local tax has significant influence to local own source revenue whereas local retribution does not have any significant influence to the local own source revenue, meanwhile local retribution does not have any significant influence to the local own source revenue and local tax and local retribution simultaneously have significant influence to the local own source revenue.Keywords: Budget target, budget realization, local revenue, local own source.